Hepatic Failure and Hyperbilirubinemia Secondary to Hemolytic Disease of the Newborn - Matthew Reinhardt; Marya L. Strand; Dajana Sabic (Hindawi Limited, 2024)
Anti-D antibody is the most common cause of hemolytic disease of the newborn (HDN). Other antigens have emerged, causing significant damage to the newborn. We report a case of a 31-week dichorionic diamniotic twin born emergently to a mother with anti-C and anti-D antibodies who required multiple percutaneous umbilical cord blood sampling (PUBS) and transfusions. Extensive resuscitation at birth was required due to severe anemia, hypovolemia, and prematurity. Ensuing liver damage occurred with subsequent profound coagulopathy, transaminitis, and direct hyperbilirubinemia that required significant support. This patient developed several unique findings including the inability to monitor oxygen saturations due to dermal bilirubin deposits and staining of baby teeth. This case report highlights the importance of early identification of additional Rh antibodies due to concern for development of more severe forms of HDN.